ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH SDN 0401 PASAR UJUNG BATU DAN KEPALA SEKOLAH SDN 0701 ROTANSOGO - Pasaribu, Rosida Minta Ito; Lubis, Aminah; Manihuruk, Waldio; Winara, Dr.; Lubis, Wildansyah (Jurnal Merah Putih Sekolah Dasar, 2024)
Finding out how principals of different schools lead their schools was the driving force for this research. This study used a phenomenological approach to qualitative research. Teachers from SDN 0701 Rotansogo and SDN 0401 Pasar Ujung Batu participated in this study. Observation, interviews, and documentation were the methods utilized to gather data. Data analysis strategies utilizing data reduction, data display, and conclusions. The research found that there are essentially three distinct types of leadership: authoritarian, democratic, and free-form. The principal at SDN 0401 Pasar Ujung Batu and SDN 0701 practices democratic leadership. This can be seen in the principal's decision-making process, which is based on approval and deliberation from subordinates. The principal treats subordinates fairly and does not discriminate based on their backgrounds. The principal listens to criticism, suggestions, and opinions, both during and outside of meetings. They also use subordinates' input to make decisions. Lastly, the principal collaborates with subordinates, as demonstrated by their participation in all school activities. Lastly, the principal has a well-established relationship with their subordinates. A transactional leadership style, in which the principal primarily served as a supervisor, coordinator, and evaluator of team performance.Keywords : Leadership Style, Principal, Democratic, Transactional